Design and Optimization of Omeprazole-Curcumin-Loaded Hydrogel Beads Coated with Chitosan for Treating Peptic Ulcers - Eman J. Heikal; Rashad M. Kaoud; Shadeed Gad; Hatem I. Mokhtar; Afaf A. Aldahish; Wafa Ali Alzlaiq; Sawsan A. Zaitone; Yasser M. Moustafa; Taha M. Hammady (MDPI AG, 2023)
This study aimed to formulate a pharmaceutical dosage form containing omeprazole (OMP) and curcumin (CURC) to treat experimental peptic ulcers. OMP and CURC were preliminarily complexed with hydroxypropyl-β-cyclodextrin for enhancing their solubilization. After that, the combined complex (CURC/OMP) was loaded to alginate beads to sustain their release and then coated with chitosan. Finally, we tested the anti-ulcerogenic impact of the best formula versus free OMP or OMP-only-loaded beads. The formulated spherical beads' diameter ranged from a minimum value of 1.5 ± 0.08 mm to 2.6 ± 0.24 mm; the swelling results ranged from 400.00 ± 8.5% to 800.00 ± 6.2%. The entrapment efficiency was in a range from 60.85 ± 1.01% to 87.44 ± 1.88%. The optimized formula (F8) showed a maximum EE% (87.44 ± 1.88%), swelling (800.00 ± 6.2%), and diameter in the range of 2.60 ± 0.24, with a desirability of 0.941. In the first hour following the administration of the free drug complex, 95% of OMP and 98% of CURC were released. This is unacceptable for medications that require a delayed release in the stomach. The initial drug release from hydrogel beads was 23.19% for CURC and 17.19% for OMP after 2 h and 73.09% for CURC and 58.26% for OMP after 12 h; however, after 24 h, 87.81% of CURC and 81.67% of OMP had been released. The OMP/CURC beads showed a more stable particle size (0.52 ± 0.01 mm) after 6 weeks. In conclusion, the OMP/CURC hydrogel beads give stronger anti-ulcer effectiveness compared to free OMP, CURC-only beads, and OMP-only-loaded beads, indicating a prospective application for managing peptic ulcers.